The Effect Of Company Size, Leverage, Profitability And Liquidity On Company Value In The Health Sector Listed On The Indonesia Stock Exchange - Yahya, Ahmad Akbar; Wuryani, Eni; Aini Haron, Nur Quratun (International Economic Conference of Business and Accounting, 2024)
The main objective of this study is to examine how company size, leverage, profitability, and liquidity affect the value of health sector companies listed on the Indonesia Stock Exchange. A total of 12 companies were selected as samples for this study, and 36 financial statements were used to meet the research criteria. The sampling technique used was purposive sampling. For data analysis, researchers used multiple linear regression and analyzed using SPSS software.The results of hypothesis testing show that leverage has a negative effect on firm value. On the other hand, company size, profitability, and liquidity were found to have no effect on the value of companies in the health sector.